Pengaruh Pemasaran Digital, Kualitas Layanan Elektronik dan Citra Merek terhadap Keputusan Konsumen Menggunakan Aplikasi Ovo - Nurul Sriminarti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The behavior of digital wallet users in Indonesia depends on individual preferences, user habits, and other factors. Consumers' decisions in using digital finance applications are influenced by various factors, including digital marketing, the quality of electronic services and the brand image of the digital finance applications they use. This research aims to determine the influence of digital marketing, electronic service quality and brand image on consumer decisions to use the OVO application in the Jabodetabek area. The method used in this research is a quantitative method that is associative. Data was collected using a questionnaire distributed via Google Form to 155 respondents who used the OVO application. The sampling technique uses purposive sampling. Data processing in this research used the IBM Statistical Package for the Social Sciences (SPSS) ver.25. Based on the results of hypothesis testing, it shows that: (1) digital marketing variables have a positive and significant effect on consumer decisions to use the OVO application (2) electronic service quality variables have a positive and significant effect on consumer decisions to use the OVO application (3) brand image variables have a positive and significant effect on consumer decisions to use the OVO application and (4) digital marketing variables, electronic service quality and brand image together have a significant influence on consumer decisions to use the OVO application.